Preparatory longswings preceding Tkachevs on uneven bars - Manning, M.; Irwin, G.; Kerwin, D.; Gittoes, M. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The preparatory longswing on uneven bars is fundamental to the development of more complex skills in women`s gymnastics. The preceding longswing governs the release parameters that in turn determine the success of the straddle Tkachev (Arampatzis & Brüggemann, 2001). Of the many longswing variations currently in use in women`s gymnastics, this study aims to investigate differences in the biomechanics of three distinctive preparatory longswings used in performing the straddle Tkachev. The long term purpose is to increase understanding of these skills and potentially improve the effectiveness of coaching.